Pengaruh Dosis Inokulum Azolla, Fosfat Alam dan Abu Sekam terhadap Sifat Fisika Tanah dan Hasil Padi pada Alfisols - Vivit Nurcahyani; Sumarno Sumarno; Sudadi Sudadi (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2014)
TITLE : THE EFFECT OF AZOLLA INOCULUM, PHOSPHATE ROCK AND RICE HULL ASH DOSAGES ON RICE YIELD AND SOIL PHYSICAL OF ALFISOLS. The use of agrochemical materials to increase rice yield in a long term may cause soil, environment damages and have low productivity. One of the ways to increase the rice yield and improve soil health is organic rice cultivation by applaying organic fertilizer inputs derived from azolla. This research objective is to find out the effect of azolla, phosphate rock and husk ash dosages, as well as the best combination of azolla, rock phosphate and husk ash which is best for soil physical and yield of rice on Alfisols. The experimental design used was Completely Randomized Design (CRD), consists of 5 treatment and repeated 5 times. Data analysis using the F test (Fisher test) with 95% level confidence. Variables measured were field capacity, maximum moisture content, bulk density, aggregate stability, plant height, dry weight of harvest rice and milled rice. The results showed the treatment combination of azolla 250 g m-2, rock phosphate equivalent with 150 kgha-1 SP-36 and husk ash equivalent with 100 kgha-1 KCl give the highest aggregate stability.